An international analysis of dividend smoothing - Javakhadze, David; Ferris, Stephen P.; Sen, Nilanjan (Journal of Corporate Finance, 2014)
This study examines the extent to which agency-based models and asymmetric information theories explain dividend smoothing around the world. Tests on a cross-section of more than two thousand firms from twenty-four countries show that managers of firms with low market-to-book ratios and less cash engage in greater dividend smoothing. Further, firms with highly-concentrated ownership structure and strong corporate governance smooth dividends less. In addition, managers of firms in industries facing high levels of competition smooth dividends more. We also determine that the extent of legal protections provided to shareholders and the culture of the country in which the firm is incorporated, as well as tax regime, have additional explanatory power for dividend smoothing. Our results are most consistent with the simultaneous presence of agency and information asymmetry effects in the decision to smooth dividends.